Deep‐Submicrometer Complementary Metal‐Oxide‐Semiconductor Transistors Based on Carbon Nanotube Films. (7th November 2021) - Shi, Huiwen; Ding, Li; Zhong, Donglai; Peng, Lian‐Mao; Zhang, Zhiyong
Abstract: Semiconducting carbon nanotube (CNT) films are considered promising channel materials for constructing complementary metal‐oxide semiconducting (CMOS) field‐effect transistors (FETs) for future high‐performance integrated circuits (ICs). However, the poor performance of short channel n‐type FETs built on solution‐derived CNT films hinders the development of truly symmetric CMOS FETs, especially as the gate length scales down to the submicrometer region. The performance of short channel n‐type FETs is improved here by using scandium contacts accompanied by a doping channel and high‐performance and symmetrical CMOS FETs with a deep submicrometer gate length are fabricated for the first time. The n‐type and p‐type CNT FETs with a 150 nm gate length exhibit a maximum on‐state current I on of ≈270 µA µm −1 and a peak transconductance g m of over 100 µS µm −1, representing the best CNT CMOS FETs thus far. Digital circuit and system benchmarking with the Intel circuit model indicates that the deep‐submicrometer CNT CMOS FETs show great advantages over the previously reported CMOS ICs based on CNT FETs or other semiconducting film‐based FETs. Abstract : The poor performance of short channel n‐type field‐effect transistors (FETs) built on solution‐derived carbon nanotube (CNT) films hinders the development of symmetric complementary metal‐oxide semiconducting (CMOS) FETs, especially in the sub‐μm region. By using scandium contacts accompanied by a doping channel, high‐performance and symmetrical CMOS FETs with a deep sub‐μm gate length are fabricated for the first time.